Analisis Desain Ergonomis Ruang Penyimpanan Rekam Medis Di RSD Nganjuk Tahun 2022 - Arya Yuniar Putra Pratama; Angga Rahagiyanto; Rossalina Adi Wijayanti; Gandu Eko Julianto Suyoso (Indonesian Journal Publisher, 2024)
The existing ergonomic arrangement of the medical records room at Nganjuk Regional Hospital (RSD) is currently encountering several challenges, including non-compliance with requirements and inefficient utilization of storage space. These issues involve inadequate shelving and the mismatch of officers' chairs and tables with their anthropometry, leading to discomfort and restricted movement during their duties. This study aims to scrutinize the ergonomic design of the medical record storage room at Nganjuk Regional Hospital in 2022, using qualitative research methods like observation, interviews, documentation, and brainstorming. The research adopts the anthropometric approach to ensure the medical record storage layout at Nganjuk Regional Hospital meets established ergonomic standards. By adjusting shelves, chairs, and tables based on officers' body sizes and proportions, the workspace becomes more comfortable and tailored to their physical needs. The research outcomes include reshaping shelves, chairs, and tables according to officers' anthropometry, along with the recommendation for 70 racks. Additionally, the recording room's reorganization is planned with a more ergonomic layout, covering 252 square meters to accommodate 63 racks.